How Can the Government Utilize Elites & Celebrities to manage Global Public Opinion on Egypt? An Exploratory Study of Mo Salah & Egypt - Ibrahim, Sara S (AUC Knowledge Fountain, 2023)
With Egypt’s latest global reputation index, nation brand, and soft power indices scoring low, such rankings have left room for finding new ways of enhancing Egypt’s global public opinion and reputation. This study showcases an untapped potential for enhancing a nation’s reputation and public opinion. This untapped potential lies in the power of elite commentary and celebrity activity. Such commentary and activity influence public opinion of the celebrity but also subsequently affect the public opinion of their country-of-origin nations. With a global phenomenon such as football player Mo Salah, it has always been suggested that his performance positively affected Egypt's public opinion. Such a hypothesis has been suggested by Egyptians but has never been tested. This study is testing existing hypotheses through the commentary of the elites and how public opinion is shaped through such commentary around Mo Salah. This developed public opinion about Mo Salah assessed how the public opinion of Egypt could be affected too. As a result, elite commentary leading to public opinion on Mo Salah indeed enhanced the public opinion of Egypt. It led to an awareness of 35 times more in 2022 in the UK than before his joining Liverpool F.C. The sentiment of how public opinion through the lens of elites’ social media commentary and celebrity activity, was the main measurement of the impact on the public opinion of Egypt. The study showed that elite commentary on Mo Salah is highly significant in the development of public opinion about Mo Salah. There has been also a significant correlation between the public opinion on Mo Salah and the public opinion on Egypt accordingly. Subsequently, the study develops policy recommendations around how social media, elite commentary, and public opinion/reputation activities could be developed for enhancing the public opinion of Egypt. The policy recommendation based on such a finding is the development of the Egyptian Council of Public Opinion & Nation Branding. Such initiation of this council has its core around integrating the elite’s commentary around events in Egypt. Another recommendation is for nurturing more talents like Mo Salah locally and globally, ensuring their exposure through the lens of the elites on social media, media outlets, and beyond.